Total synthesis and absolute configuration determination of the α-glycosidase inhibitor (3S,4R)-6-Acetyl-3-hydroxy-2,2-dimethylchroman-4-yl (Z)-2-Methylbut-2-enoate from Ageratina grandifolia - Dandawate, Monica; Choudhury, Rahul; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Journal of Natural Products, 2023)
Herein, we report the first total synthesis of & alpha;-glycosidaseinhibitor (3R, 4S)-6-acetyl-3-hydroxy-2,2-dimethylchroman-4-yl(Z)-2-methylbut-2-enoate as well as its enantiomer.Our synthesis confirms the chromane structure separately proposedby Navarro-Vazquez and Mata, on the basis of DFT computations. Furthermore,our synthesis allowed us to determine the absolute configuration ofthe natural compound as (3S, 4R)and not (3R, 4S).